2010
DOI: 10.1152/jn.00839.2009
|View full text |Cite
|
Sign up to set email alerts
|

Presynaptic Modulation of Ia Afferents in Young and Old Adults When Performing Force and Position Control

Abstract: Baudry S, Maerz AH, Enoka RM. Presynaptic modulation of Ia afferents in young and old adults when performing force and position control. J Neurophysiol 103: 623-631, 2010. First published November 25, 2009 doi:10.1152/jn.00839.2009. The present work investigated presynaptic modulation of Ia afferents in the extensor carpi radialis (ECR) when young and old adults exerted a wrist extension force either to support an inertial load (position control) or to achieve an equivalent constant torque against a rigid rest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
69
2
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 82 publications
(83 citation statements)
references
References 40 publications
8
69
2
4
Order By: Relevance
“…Therefore, the impact of the afferent feedback on the agonist and antagonist motor neuron populations is reduced, although it is possible that an increased gamma drive may increase spindle output and thereby in part compensate for the decreased synaptic gain (Llewellyn et al 1990;. Baudry et al (2010) showed that young subjects increased the afferent gain when exposed to a more unstable task, whereas older subjects, who are less able to modulate presynaptic inhibition (Butchart et al 1993;Koceja and Mynark 2000), reacted with an increase in the cocontraction level. These observations suggest that cocontraction can be considered a more easily applied strategy that is often the first choice when a subject is exposed to an unknown environment, whereas it is more difficult, but also more desirable because of metabolic costs, to adjust the afferent gains to the appropriate level.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the impact of the afferent feedback on the agonist and antagonist motor neuron populations is reduced, although it is possible that an increased gamma drive may increase spindle output and thereby in part compensate for the decreased synaptic gain (Llewellyn et al 1990;. Baudry et al (2010) showed that young subjects increased the afferent gain when exposed to a more unstable task, whereas older subjects, who are less able to modulate presynaptic inhibition (Butchart et al 1993;Koceja and Mynark 2000), reacted with an increase in the cocontraction level. These observations suggest that cocontraction can be considered a more easily applied strategy that is often the first choice when a subject is exposed to an unknown environment, whereas it is more difficult, but also more desirable because of metabolic costs, to adjust the afferent gains to the appropriate level.…”
Section: Discussionmentioning
confidence: 99%
“…Simultaneous activation of antagonist muscles, however, not only is a strategy used to achieve stability but is also necessary to perform certain movements. For example, the extensor and flexor carpi radialis are antagonists with respect to wrist flexion/extension but act as synergistic muscles during radial deviation of the wrist (Baudry and Enoka 2009). This implies that the cocontraction of antagonist muscles and stretch-sensitive afferent feedback should not be considered only as alternative strategies to achieve stability, as they often need to coexist and be tuned to reach the optimal compromise for output steadiness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because aging is associated with declines in sensory sensitivity, slowing of conduction velocity, and reductions in the amplitude of the responses evoked in spinal pathways (Burke and Kamen 1996;Chung et al 2005;Corden and Lippold 1996;Kido et al 2004;Nadler et al 2002;Tang and Woollacott 1999), old adults modulate afferent feedback less than young adults when performing voluntary actions and tend to rely more on adjusting levels of agonist and antagonist coactivation (Baudry et al 2010). For example, old adults limit the gain of responses arising from the muscle spindle relative to young adults in response to changes in posture and accompanying muscle contractions (Angulo-Kinzler et al 1998;Tsuruike et al 2003) by modulating presynaptic inhibition of Ia afferents less when proceeding from rest to a submaximal contraction (Butchart et al 1993;Earles et al 2001;Morita et al 1995) and when changing from a supine to a standing posture (Koceja and Mynark 2000), and they use less reciprocal Ia inhibition during movement (Hortobágyi et al 2006;Kido et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…To provide insight on age-associated adaptations in the integration of synaptic input by motoneurons, the approach focused on the discharge characteristics of the motor units when they were recruited during sustained con-tractions with different inertial loads. Because of the greater reliance by old adults on agonist-antagonist coactivation rather than modulation of spinal reflex pathways when confronted with a change in load compliance (Baudry et al 2010), the hypothesis was that old adults would exhibit less modulation of motor unit discharge across the two inertial loads than young adults.…”
mentioning
confidence: 99%